PENERAPAN PEMBELAJARAN KOOPERATIF DENGAN FORMASI REGU TEMBAK UNTUK MENINGKATKAN MINAT BELAJAR IPA FISIKA SISWA KELAS VIII DI SMP NEGERI 34 PEKANBARU - Nor, Muhammad; Irianti, Mitri; ', Yuniarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to determine the increase in interest in learning physics science students of SMP Negeri 34 Pekanbaru through the implementation of cooperative learning with the a firing line and to know the interest to learn physics science eighth grade students of SMP 34 Pekanbaru between the implementation of a firing line strategies in cooperative learning with learning conventional. The subjects were students of class VIII2 which 40 students and VIII3 with 39 students. In conducting the research, the researcher used Quasi Eksperimental Design as the method of research with Nonequivalent Control Group design. Data collection instrument in this research was a questionnaire interest in learning physics science students consisting of 26 statements. Data were analyzed with descriptive analysis techniques to see increased student interest of the gain and inferential analysis to see significant value. The results of this research indicate students interest increased by 0.14 in the low category. It can be concluded that the application of a firing line strategies in cooperative learning can increase students interest in the material of optical instruments in class VIII SMP Negeri 34 Pekanbaru.Keywords:Interest in Learning, Firing Line, Optical Instruments